An optimization study on transesterification catalyzed by the activated carbide slag through the response surface methodology. (1st March 2015) - Liu, Mengqi; Niu, Shengli; Lu, Chunmei; Cheng, Shiqing
Highlights: New catalyst material for biodiesel production. New utilization approach of waste carbide slag. Detailed characterization of carbide slag used as transesterification catalyst. Optimal parameters for biodiesel production obtained by response surface methodology. Effect of impurities on catalytic activity of carbide slag in transesterification. Abstract: After activated at 850 °C under air condition, calcium hydroxide and calcium carbonate in carbide slag are transformed into calcium oxide. The prepared transesterification catalyst, labeled as CS-850, gains surface area of 8.00 m 2 g −1, functional groups of vanishing OCO and OH bonds, surface morphology of tenuous branch and porous structure and basic strength of 9.8 < H – < 15.0. From aspects of the molar ratio of methanol to oil ( γ ), the catalyst added amount ( ζ ) and the reaction temperature ( T r ), transesterification catalyzed by CS-850 is optimized through the Box–Behnken design of the response surface methodology (BBD–RSM). A quadratic polynomial model is preferred for transesterification efficiency prediction with coefficient of determination ( R 2 ) of 0.9815. The optimal parameters are predicted to be γ = 13.8, ζ = 6.7% and T r = 60 °C with the efficiency of 94.70% and validated by experimental value of 93.83%. Meanwhile, γ is demonstrated to be the most significant variable for the minimum p - value . Besides, CS-850 performs acceptable reusability and for the fifth time reusage, efficiency of 82.61% could still be supplied. Aluminium oxide is proved to have the greatest effect on the catalytic activity of CS-850 among other small quality oxides. Physicochemical properties of the purified biodiesel meet American Society for Testing and Material (ASTM) standard.